Climate change in Switzerland: a review of physical, institutional, and political aspects. (24th March 2014) - Brönnimann, Stefan; Appenzeller, Christof; Croci‐Maspoli, Mischa; Fuhrer, Jürg; Grosjean, Martin; Hohmann, Roland; Ingold, Karin; Knutti, Reto; Liniger, Mark A.; Raible, Christoph C.; Röthlisberger, Regine; Schär, Christoph; et al.
Abstract : Climate change is clearly discernible in observed climate records in Switzerland. It impacts on natural systems, ecosystems, and economic sectors such as agriculture, tourism, and energy, and it affects Swiss livelihood in various ways. The observed and projected changes call for a response from the political system, which in Switzerland is characterized by federalism and direct democratic instruments. Swiss climate science embraces natural and social sciences and builds on institutionalized links between researchers, public, and private stakeholders. In this article, we review the physical, institutional, and political aspects of climate change in Switzerland. We show how the current state of Swiss climate science and policy developed over the past 20 years in the context of international developments and national responses. Specific to Switzerland is its topographic setting with mountain regions and lowlands on both sides of the Alpine ridge, which makes climate change clearly apparent and for some aspects (tourist sector, hydropower, and extreme events) highly relevant and better perceivable (e.g., retreating glaciers). Not surprisingly the Alpine region is of central interest in Swiss climate change studies. This article is categorized under: Trans‐Disciplinary Perspectives > National Reviews